Optimizing administrative datasets to examine acute kidney injury in the era of big data: workgroup statement from the 15th ADQI Consensus Conference. Issue 1 (December 2016) - Siew, Edward; Basu, Rajit; Wunsch, Hannah; Shaw, Andrew; Goldstein, Stuart; Ronco, Claudio; Kellum, John; Bagshaw, Sean
Abstract Purpose of review The purpose of this review is to report how administrative data have been used to study AKI, identify current limitations, and suggest how these data sources might be enhanced to address knowledge gaps in the field. Objectives 1) To review the existing evidence-base on how AKI is coded across administrative datasets, 2) To identify limitations, gaps in knowledge, and major barriers to scientific progress in AKI related to coding in administrative data, 3) To discuss how administrative data for AKI might be enhanced to enable" communication" and "translation" within and across administrative jurisdictions, and 4) To suggest how administrative databases might be configured to inform 'registry-based' pragmatic studies. Source of information Literature review of English language articles through PubMed search for relevant AKI literature focusing on the validation of AKI in administrative data or used administrative data to describe the epidemiology of AKI. Setting Acute Dialysis Quality Initiative (ADQI) Consensus Conference September 6-7th, 2015, Banff, Canada Patients Hospitalized patients with AKI Key messages The coding structure for AKI in many administrative datasets limits understanding of true disease burden (especially less severe AKI), its temporal trends, and clinical phenotyping. Important opportunities exist to improve the quality and coding of AKI data to better address critical knowledge gaps in AKI and improve care. Methods A modified Delphi consensus building process consisting of review of the literature and summary statements were developed through a series of alternating breakout and plenary sessions. Results Administrative codes for AKI are limited by poor sensitivity, lack of standardization to classify severity, and poor contextual phenotyping. These limitations are further hampered by reduced awareness of AKI among providers and the subjective nature of reporting. While an idealized definition of AKI may be difficult to implement, improving standardization of reporting by using laboratory-based definitions and providing complementary information on the context in which AKI occurs are possible. Administrative databases may also help enhance the conduct of and inform clinical or registry-based pragmatic studies. Limitations Data sources largely restricted to North American and Europe Implications Administrative data are rapidly growing and evolving, and represent an unprecedented opportunity to address knowledge gaps in AKI. Progress will require continued efforts to improve awareness of the impact of AKI on public health, engage key stakeholders, and develop tangible strategies to reconfigure infrastructure to improve the reporting and phenotyping of AKI. Why is this review important? Rapid growth in the size and availability of administrative data has enhanced the clinical study of acute kidney injury (AKI). However, significant limitations exist in coding that hinder our ability to better understand its epidemiology and address knowledge gaps. The following consensus-based review discusses how administrative data have been used to study AKI, identify current limitations, and suggest how these data sources might be enhanced to improve the future study of this disease. What are the key messages? The current coding structure of administrative data is hindered by a lack of sensitivity, standardization to properly classify severity, and limited clinical phenotyping. These limitations combined with reduced awareness of AKI and the subjective nature of reporting limit understanding of disease burden across settings and time periods. As administrative data become more sophisticated and complex, important opportunities to employ more objective criteria to diagnose and stage AKI as well as improve contextual phenotyping exist that can help address knowledge gaps and improve care. ABRÉGÉ Article synthèse Cette revue vise à rendre compte de la manière dont les données administratives ont été utilisées jusqu'à maintenant pour l'étude de l'insuffisance rénale aiguë (IRA). On a également voulu définir les limites actuelles et suggérer une manière dont les sources de données pourraient être améliorées pour pallier les lacunes des connaissances dans ce domaine. Objectifs de la revue Cette revue visait plusieurs objectifs: 1) Répertorier les données probantes sur la manière dont l'IRA est codée dans les ensembles de données administratives. 2) Identifier les limites, les lacunes au niveau des connaissances et les principaux obstacles aux avancées de la science relevant de la codification de l'IRA dans les données administratives. 3) Discuter de la façon dont les données administratives relatives à l'IRA pourraient être bonifiées afin de favoriser leur transmission au sein des différents secteurs de compétences. 4) Suggérer une nouvelle façon de configurer les bases de données administratives afin qu'elles puissent servir de source d'information pour la tenue d'études pragmatiques fondées sur la consultation de registres. Sources L'information a été colligée à la suite d'un passage en revue des articles pertinents publiés en anglais sur PubMed. Les articles portant sur la validation de l'IRA au sein des données administratives ou sur l'usage de celles-ci pour rendre compte de l'épidémiologie de l'IRA ont été retenus. Cadre de la revue La revue a eu lieu dans le cadre de la 15e réunion annuelle de concertation de l'Acute Dialysis Quality Initiative (ADQI) qui s'est tenue les 6 et 7 septembre 2015 à Banff, au Canada. Population observée Les cas retenus pour la revue sont ceux de patients hospitalisés atteints d'IRA. Points saillants La façon dont l'IRA est codée au sein des ensembles de données limite la compréhension réelle du fardeau que représente cette maladie, particulièrement pour les patients atteints moins sévèrement. Il semble également que l'on ne puisse identifier correctement les tendances temporelles ni le phénotype clinique de l'IRA parmi ces données. On a aussi constaté qu'il existe d'importantes possibilités d'amélioration de la codification de l'IRA dans les ensembles de données pour arriver à mieux cerner les lacunes dans la connaissance de la maladie et bonifier les soins prodigués aux patients. Méthodologie Une version adaptée de la méthode Delphi pour l'atteinte d'un consensus a été utilisée pour produire le compte-rendu. La revue de la littérature et des récapitulatifs ont été élaborés à la suite d'une série de discussions alternant entre des ateliers en petits groupes et des séances plénières. Résultats Les codes administratifs concernant l'IRA sont limités en raison du faible taux de rappel des documents pertinents lors des recherches, du manque de normalisation dans le classement de la sévérité de la maladie et de la faible identification de son phénotype. Ces limites sont de plus freinées par un manque de sensibilisation des fournisseurs de soins de santé face à l'IRA et par le caractère subjectif d'un signalement volontaire des cas observés. Bien qu'une définition idéalisée de l'IRA soit difficile à mettre en œuvre, améliorer la normalisation des signalements en se basant sur un consensus scientifique et fournir de l'information quant au contexte où se manifeste l'IRA sont possibles. Les bases de données administratives peuvent améliorer les pratiques entourant la conduite d'études cliniques ou d'études pragmatiques basées sur la consultation de registres, et servir de sources d'informations pour celles-ci. Limites de la revue La provenance des sources consultées pour cette revue se limite en grande partie à l'Amérique du Nord et à l'Europe. Conclusions La croissance et l'évolution rapide des bases de données administratives représentent une occasion unique de s'attaquer aux lacunes dans les connaissances sur l'IRA. L'avancement de ces connaissances demandera le déploiement d'efforts constants pour favoriser la prise de conscience des répercussions de cette maladie sur la santé publique. Cela demandera aussi l'engagement des principaux intervenants ainsi que la mise en place de stratégies concrètes visant la reconfiguration des infrastructures existantes et l'amélioration de la collecte de données et de l'identification du phénotype de l'IRA.